FRENCH APPELLATIONS IN THE NOVEL WAR AND PEACE BY LEV TOLSTOY / LES FORMES D`APPELLATION FRANCAISES DANS LE ROMAN DE LEV TOLSTOI GUERRE ET PAIX (fr) - S. Мaire (Вестник Кемеровского государственного университета, 2015)
The paper discusses the novel of Lev Tolstoy examining French appellations and addresses used in the novel from the point of view of their evolution in the text and use in different communicative situations. The author comes to the conclusion that French appellations and addresses are evidence of the negative estimation of the characters by Lev Tolstoy.